Inheritance agreement: harmonization with the law of the European Union - Trufanova, Yuliia; Yatsenko, Khrystyna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
At present, work is underway to harmonize the norms of national civil law with the legal norms of European and international law. In most countries of the European Union the institution of inheritance agreement is quite common, and the procedure for its conclusion and implementation is regulated in detail, in contrast to our country, where the inheritance agreement is still inferior in regulation to established institutions of inheritance law - inheritance by law and inheritance by will. This necessitates a legal analysis of the main provisions of European and national legal regulation of the inheritance agreement. The implementation of the inheritance agreement is conditioned by the needs of the present and confirmed by the practice of application in the countries of the European Union. Given its legal structure, the lack of a common scientific position on the legal nature of the inheritance agreement, its ambiguity and lack of consistent case law on the application of this institution, the inheritance agreement is an extremely relevant topic for research in scientific terms. This necessitates a legal analysis of the main provisions of European and national legal regulation of the inheritance agreement and identify common and distinctive features of this institution, which will identify gaps in Ukrainian legal regulation and find ways to transform, modernize and bring national standards in line with European and international standards. Thus, given the European integration aspirations of our country, the harmonization of the institution of the inheritance treaty with the norms of the European Union is a topical issue today. The model of inheritance agreement under the civil law of Ukraine differs significantly from its counterpart in foreign law, where the inheritance agreement is aimed primarily at appointing an heir and is considered along with inheritance by will and law as the basis of inheritance and, accordingly, creates inheritance The introduction of European legislation into domestic practice, in particular the harmonization of civil law with the norms of the European Union, is necessary for the effective use of this legal structure and to fill the gaps in national legislation in the field of inheritance contract regulation.